The Efficacy of an Extracurricular Inquiry Programme on Grade 8 and 9 South African Low Quintile Learners' Science Learning. Issue 2 (4th May 2019) - Stott, Angela Elisabeth
Abstract : Physical sciences teachers in low-quintile South African schools avoid the use of inquiry on the grounds of inefficiency and ineffectiveness for test preparation. This avoidance is consistent with the view that the high cognitive load inquiry offers to extreme novices such as these learners may be prohibitive. Given the purported benefits of inquiry, this situation seems lamentable, but until empirical evidence is found to the contrary, the applicability of inquiry in this context appears an impractical ideal. In this study I begin the search for evidence of benefits of inquiry for the education of learners from such backgrounds, albeit within an educational setting atypical of the context. I investigate the effectiveness of a week-long inquiry holiday programme for 26 Grade 8 and 9 learners from low-quintile schools and the predictive value of their Natural Sciences marks for success in the programme. The findings show statistically significant learning gains from pre- to post-test scores and pre- to delayed post-test scores, as well as strong correlations between the learners' Natural Sciences marks and the post-test scores. This shows that holiday inquiry programmes can be effective at promoting learning, measured by test-performance, even for learners with backgrounds of underprivilege, at least among higher achieving learners.